Lactate in ferroptosis regulation: A new perspective on tumor progression and therapy - Nan Wu; Xiaoqi Wei; Shuang Yu; Lina Yang; Xiaowen Zhang (Pharmacological Research, 2025)
Ferroptosis is a type of regulated cell death induced by iron-dependent lipid peroxidation, which is tightly regulated by metabolism. Lactate is a byproduct of glycolysis that regulates energy, fatty acid metabolism, and redox homeostasis as a fuel or signaling molecule. The role of lactate in ferroptosis occurs under different contexts. Lactate promotes ferroptosis under non-tumoral conditions, whereas in the tumor microenvironment, it can lead to tumor cell resistance to ferroptosis, thereby promoting tumor proliferation, metastasis, and drug resistance. The specific molecular mechanisms underlying lactate-regulated ferroptosis involve polyunsaturated fatty acids metabolism, antioxidant systems, iron metabolism, and mitochondrial function by lactate or lactate-induced lactylation. In addition, nanomaterials containing LOX and/or inhibition of MCTs may be used to enhance tumor cell ferroptosis in various cancers by targeting lactate metabolism. In this review, we systematically summarize the role and mechanism of lactate in ferroptosis regulation in pathophysiology, particularly in tumor progression and therapy, which provides a new perspective on tumor progression and therapy.